Survival outcomes of percutaneous endoscopic gastrostomy, comparison of cerebrovascular event and non-cerebrovascular event in malnourished patients - Küçükardalı, Yaşar; Terekeci, Murat Hakan; Yalçın, Arzu; Nurmuhammedov, Rahman; Pata, Cengiz; Temür, Sibel; Kartufan, Ferda Fatma; Şilek, Hakan; Yaltırık, Nazlı Şişik; Altunok, Elif Çiğdem (Journal of Surgery and Medicine, 2019)
Aim: The number of comorbid diseases increased with the rise in the elderly population. In some cases, the state of deficient or absent nutrition emerges. Nevertheless, the contribution of percutaneous endoscopic gastrostomy (PEG) to the quality of life and the survival rate in the elderly with certain diseases remains controversial. Methods: In this prospective cohort study, patients who underwent percutaneous endoscopic gastrostomy (PEG) procedure between 2009 and 2015 were divided into two groups: CVE group consisted of patients with cerebrovascular event (CVE) and non-CVE group comprised patients who suffered from esophageal tumors, head and neck tumors, brain tumors, amyotrophic lateral sclerosis and terminal dementia. In this study, the patients’ pre-PEG and post-PEG body mass index (BMI) values, hemoglobin (Hb), albumin (alb), creatinine (Cr) and C-reactive protein (CRP) values, white blood cell counts, demographic characteristics, 30, 90, 180 and 365 day-survival rates, complications (mechanical, metabolic and infectious) and duration of patency of the PEGs were compared. Results: The average age was lower while survival rate on the 90th day was higher in the CVE group. No significant difference was found in terms of other parameters. At the end of the one-year follow-up, 21% of the patients in the CVE group and 12% of those in the non-CVE group were able to be fed without PEG. Conclusion: PEG patency was higher in the CVE group at 3 months but there was no statistically significant difference between the groups at one-year and overall follow-up periods.